2015
DOI: 10.1016/j.neuroimage.2015.04.041
|View full text |Cite
|
Sign up to set email alerts
|

Sharpened cortical tuning and enhanced cortico-cortical communication contribute to the long-term neural mechanisms of visual motion perceptual learning

Abstract: Much has been debated about whether the neural plasticity mediating perceptual learning takes place at the sensory or decision-making stage in the brain. To investigate this, we trained human subjects in a visual motion direction discrimination task. Behavioral performance and BOLD signals were measured before, immediately after, and two weeks after training. Parallel to subjects' long-lasting behavioral improvement, the neural selectivity in V3A and the effective connectivity from V3A to IPS (intraparietal su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
65
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(80 citation statements)
references
References 67 publications
(88 reference statements)
13
65
2
Order By: Relevance
“…We reasoned that if training could improve the neural representations of the motion stimuli (especially in the trained direction), as suggested by the TMS and psychophysical results, it was possible that decoding accuracies for the orthogonal directions could be improved by training. Similar approaches have been used previously (19)(20)(21). Before training, a repeated-measures ANOVA revealed a significant main effect of stimulus coherence level and a significant interaction between stimulus coherence level and area [V3A and MT+; both F(1,11) > 7.87l P < 0.05; Fig.…”
Section: Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…We reasoned that if training could improve the neural representations of the motion stimuli (especially in the trained direction), as suggested by the TMS and psychophysical results, it was possible that decoding accuracies for the orthogonal directions could be improved by training. Similar approaches have been used previously (19)(20)(21). Before training, a repeated-measures ANOVA revealed a significant main effect of stimulus coherence level and a significant interaction between stimulus coherence level and area [V3A and MT+; both F(1,11) > 7.87l P < 0.05; Fig.…”
Section: Resultsmentioning
confidence: 52%
“…In contrast, Vaina and colleagues (25,26) provided neuropsychological evidence indicating that V3A and MT+ are dominant in local and global motion processing, respectively. Recently, we found that perceptual training with 100% coherent motion increased the neural selectivity in V3A (21). We also have data showing that training with 40% coherent motion increased the neural selectivity in MT+.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Changes also occur among connections linking stimulus components (Crist, Li, & Gilbert, 2001). Perceptual learning thereby improves efficiency in encoding and processing, which enhances response to stimuli (Chen et al, 2015;Li, Piech, & Gilbert, 2008).…”
mentioning
confidence: 99%
“…Neural models of perceptual learning emphasize interactions across levels of processing, particularly involving feedback from later stages that facilitate stimulus processing at early levels (Chen et al, 2015). The site of plasticity has been proposed to vary with task difficulty (reversed hierarchy theory), where less difficult tasks produce changes to high-order processing, while increased difficulty shifts plasticity to lowlevel processing specific to stimulus properties (Ahissar & Hochstein, 2004).…”
mentioning
confidence: 99%